State legal doctrines of the 19th century in theses of Kazan University - E.A. Apolski (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper analyzes the state legal doctrines contained in the master's and doctoral theses on state law defended at the Law Faculty of Kazan Imperial University in the second half of the 19th century. Three doctoral and five master's theses on state law defended in Kazan University were used as the object of study. The empirical approach to development of these works (description, classification, and systematization of the results) was employed on the basis of objectives, tasks, stages, and results obtained by investigators of state law in their works. According to the thematic classification of these works, the priority areas of scientific research explored by scientists in Kazan have been identified. The main areas are problems of the history of Russian and foreign law and state. The theoretical approach to assessment of the considered state legal doctrines from these theses has allowed us to reveal the most important regularities of their occurrence and development. The most notable of them are as follows: firstly, research carried out in the theses was not due to the accumulated source base, but because of the lack of reliable sources; secondly, scientists studying state mechanisms tend to be consistent when choosing the subject of their research, and most doctoral theses were a continuation of master's theses. The paper reveals the results formulated by the authors in their theses, which often took the form of scientific hypotheses or ideas. At the same time, it has been found that the authors often did not aim to obtain the final objective knowledge about a particular institute or a problem, but their work was assessed as a background for future research. The methodology of obtaining general theoretical knowledge in the theses considered in the paper can be used in the future to identify new patterns in the development of doctrines for other branches of jurisprudence and in other periods of the development of law and state.